Produktivitas dan Kandungan Protein Beras Mutan M6 Hasil Iradiasi Sinar Gamma pada Benih Padi Varietas Mentik Susu - Tiwi Rachmawati; Ahmad Yunus; Parjanto Parjanto (Agrotechnology Research Journal, 2023)
Mentik Susu is a popular rice germplasm in Indonesia. Due to field constraints in Mentik Susu rice cultivation, farmers switched to better varieties with higher yields. Farmers switch to superior types with high yields due to high plant posture, long harvest life, and low yields. Rice plants usually have a protein content of 4-5% per gram while without given radiation. It will be expected that after receiving gamma rays, the protein content in mutant plants will increase up to 7-8% per gram. The aim of this research was to evaluate the productivity and protein content of rice grain of 35 mutant strains of rices that could be developed into new varieties. The research took place at the Tegalgondo Rice Seed Garden Agricultural Land between June to October 2020. This research used Randomized Complete Block Design method with a single factor. Each treatment was repeated three times. The data obtained was analyzed with analysis of variance and followed with Duncan’s Multiple Range Test at a 5% level if any significant influences. The results of this research showed productivity of 35 Mentik Susu rice lines ranged from 4.28 to 6.69 ha-1, with either a high protein content ranging from 5-8% per gram and intermediate high yield potential strains G63T11-B6-T27(1), G15T5-14-B5-T60, G15T5-14-B5-T46, G11T22-19-B1-T48, G15T5-14-B3-T36, M-MS2-G15T3-2-5 -T27, M-MS2-G18T7-4-12-T13, M-MS2-G18T7-4-9-T12. These strains might be cultivated as potential candidates for new high-yielding varieties, which would then be evaluated for higher yields or multilocation tests before becoming published as new varieties.